A hybrid absorption/thermo-electric cooling system driven by a concentrated photovoltaic/thermal unit. (August 2020) - Al-Nimr, Moh'd A.; Mugdadi, Basheer
Abstract: This paper presents a novel hybrid solar cooling system driven by a concentrated photovoltaic/thermal unit (CPV/T). The electricity of the PV module is used to power the thermoelectric cooler while the thermal energy is used to run an absorption cooler. The effective cooling of the PV module provides more electricity, but less thermal energy quality (temperature). Thus, there is more cooling effect from the thermoelectric cooler and less cooling effect from the absorption cooler. The major aim of this study is to optimize the performance of the PV panel cooling in order to find the maximum total cooling effect. A mathematical model of the proposed system has been presented. The model is validated and used to investigate the performance of the system under a wide range of operating and design conditions. The results showed that less cooling of PV panel provides the maximum total cooling capacity, so in order to conduct the optimization process, the COP of the thermoelectric cooler should exceed 6.4 which implies the figure of merit to be 70. The overall COP of the system at 1000 W/m 2 increases from 0.151 to 0.233 when the PV/T outlet temperature increases from 65 to 90 °C.